Leakage Warning System and Monitoring Lapindo Sidoarjo Mud Embankment Based on Internet of Things - Haji, Shon; Ahfas, Akhmad; Syahrorini, Syamsudduha; Ayuni, Shazana Dhiya (Indonesian Journal of Artificial Intelligence and Data Mining, 2024)
The emergence of the Lapindo Sidoarjo mudflow has a long history since 29 May 2006. The point of the mudflow is in Siring Village, and until now, it has shown no signs of stopping. Sidoarjo residents are still fearful of the impact and recurrence of the mudflow, especially those still living around the embankment. The real impact is often still felt, such as embankment leaks, embankment collapses, or overflowing water mixed with mud during high rainfall, making people who still live around the embankment anxious. The unavailability of monitoring information to the public and the unclear mitigation system makes it necessary to have an information system that is easily accessible to the public. Therefore, by utilizing the advances in Internet of Things technology, this research will design a prototype system to monitor the conditions around Lapindo Sidoarjo Mud using Telegram Bot as a user interface, the ESP32-Cam microcontroller board, SW-420 vibration sensor, and MPU-6050 accelerometer sensor. The result of testing this prototype tool is that the Telegram user will receive a notification if the condition of the prototype field is experiencing vibrations or changes in position. Other than that, the Telegram user can also request real-time information, such as temperature, the axis position of the prototype as an initial benchmark, and the current photo to know the condition of the Lapindo Sidoarjo mud embankment. That way, it is hoped that this prototype system will become a monitoring and mitigation solution for the local people and the general public who reach this Telegram Bot room chat.